Complex splicing in the human T-cell leukemia virus (HTLV) family of retroviruses: novel mRNAs and proteins produced by HTLV type I. - Ciminale, V (1992)
Novel cytoplasmic mRNA species produced by human T-cell leukemia virus type I (HTLV-I) were cloned by using the polymerase chain reaction technique. Five novel 3' splice sites located in the X region and upstream of the env gene were identified. Splicing to the 3' splice sites in the X region generates mRNAs that express two previously unidentified viral proteins, named Rof and Tof. Tof accumulates in the nucleoli of transfected cells. The other viruses of the HTLV family, such as HTLV-II and bovine leukemia virus, also have a complex splicing pattern and are capable of producing additional proteins encoded in the X region. These results suggest that HTLV-I and other members of the HTLV family produce novel proteins, which may contribute to the biological properties of these viruses.